A Village-Scale Study Regarding Landscape Evolution and Ecological Effects in a Coastal Inner Harbor - Qinqin Pan; Saiqiang Li; Jialin Li; Mingshan Xu; Xiaodong Yang (Land)
The development of inner harbors has been accompanied by the destruction of natural landscapes, which in turn has led to numerous ecological problems. However, the temporal and spatial relationships between changes in the inner harbor landscape and ecological effects are not yet clear, and there are relatively few studies at smaller scales such as villages. In this study, we investigated Xieqian Harbor in Xiangshan County, along the eastern coast of China, and then analyzed the landscape change and evolutionary characteristics of the effects of carbon storage, soil conservation, and water yield at the village scale for the years 2000, 2010, and 2020. We then used the geographically and temporally weighted regression (GTWR) model to explore the spatiotemporal relationships between landscape variables and ecological effects. The results showed that the fragmentation and diversity of landscape patches increased from 2000 to 2020 due to reclamation and aquaculture, tourism development, and harbor construction, as reflected by the edge density (ED) and the Shannon diversity index (SHDI), which increased by 11.31% and 2.82%, respectively. This change resulted in a notable reduction of 572.6 thousand tons in carbon sequestration, 853 million tons in soil conservation, and 19 million cubic meters in water yield over the past 20 years. When temporal non-stationarity and spatial heterogeneity were combined, the relationship between landscape change and ecological effects became highly intricate, with varying responses across different time periods and locations. The area-weighted mean patch shape index (AWMSI) was a key factor affecting the three ecological effects. Our research confirmed that there was significant spatiotemporal heterogeneity in the effects of different landscape variables on ecological effects in inner harbors at the village scale. Compared with larger-scale studies, the results of village-scale studies revealed more precisely the impacts of localized landscape changes on ecological effects, providing support for the sustainable management of inner harbors and providing a new approach to integrating GTWR into landscape ecological time–space analysis research.